2016
DOI: 10.1002/ajmg.a.38030
|View full text |Cite
|
Sign up to set email alerts
|

Novel findings of left ventricular non‐compaction cardiomyopathy, microform cleft lip and poor vision in patient with SMC1A‐associated Cornelia de Lange syndrome

Abstract: Relatively few patients with Cornelia de Lange syndrome (CdLS) due to SMC1A mutation have been reported, limiting understanding of the full extent of the phenotype. Compared to children with classic NIPBL-associated CdLS, patients with SMC1A-associated CdLS have a milder physical phenotype with prominent intellectual disability, high rate of cleft palate and absence of limb reductions. We present a patient with SMC1A-associated CdLS who had typical features including developmental delay, seizure disorder, feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
4
10
0
1
Order By: Relevance
“…SMC1A mutations can cause early onset epilepsy only in females with cluster seizures. At present, a spectrum of SMC1A gene have been related with Cornelia de Lange syndrome (CdLS), SMC1A-related encephalopathy only with female patients, colorectal carcinomas, bladder cancer and leukemia [15][16][17][18][19][20][21][22]. Consistent with previous clinical reports, our 3 patients have moderate to severe neurological impairment and epilepsy.…”
Section: Discussionsupporting
confidence: 89%
“…SMC1A mutations can cause early onset epilepsy only in females with cluster seizures. At present, a spectrum of SMC1A gene have been related with Cornelia de Lange syndrome (CdLS), SMC1A-related encephalopathy only with female patients, colorectal carcinomas, bladder cancer and leukemia [15][16][17][18][19][20][21][22]. Consistent with previous clinical reports, our 3 patients have moderate to severe neurological impairment and epilepsy.…”
Section: Discussionsupporting
confidence: 89%
“…CHD with SMC1A -associated CdLS has been previously reported in 13 cases, including ours, yet this is the first report including a TGA diagnosis (Supplementary Table 1) 24,6,1218 . In patients with CHD, the rate of substitution or mutation at an arginine position is 42% (5/12), and in patients without CHD, the rate is 50% (11/22).…”
mentioning
confidence: 69%
“…A review of the literature revealed 60 cases of SMC1A -associated CdLS with a male-to-female ratio of 1:2 3 . A total of nine cases of CdLS with congenital cardiac defects (CHD) have been reviewed 4 , although the incidence of CHD in patients with CdLS is ~30% 5 . SMC1A -related CdLS arises from a dominant negative effect in females 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, cases have been increasingly reported of females with heterozygous de novo SMC1A pathogenic variants, mostly loss-of-function mutations (LOFs). These variants are associated with a more severe clinical phenotype of developmental and epileptic encephalopathy (DEE), a devastating form of early onset intractable epilepsy beginning in infancy and associated with global developmental delay, cognitive dysfunction, and ongoing epileptiform activity [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Most reported cases did not show significant brain MRI abnormalities, but cases with holoprosencephaly have been reported [ 15 , 23 ].…”
Section: Introductionmentioning
confidence: 99%